Physiological responses and phytochemical composition of Gynura procumbens (Lour.) Merr. affected by shade and plant density - Ahmed, Omar Ali (2020)
Gynura procumbens (Lour.) Merr., locally known as Sambung Nyawa, has been documented to possess high phytochemicals. Light intensity and plant density are known parameters that affect composition and quantity of phytochemicals in plants. The present 3-part study examined the effects of these parameters on growth and development of G. procumbens aimed at producing higher biomass yield with consistently high secondary metabolite contents. The first experiment was conducted to determine the effects of four levels of shades (0, 30, 50 and 70%) on growth, physiological attributes, biomass yield and phytochemical contents using nested design with four replications. Results showed significant effects of shade levels on plants grown under 30% shade recording high total leaf fresh weight (TLFW), total fresh weight (TFW), total leaf dry weight (TLDW) and total dry weight (TDW), with increased number of branches and higher crop growth rate. Control treatment (0% of shade) revealed the lowest fresh and dry biomass yield in TLFW, TFW, TLDW and TDW corresponding to low net photosynthesis rate, total chlorophyll content, leaf area and number of branches. Total phenol, flavonoid contents, C/N ratio and antioxidant activities decreased with increase in shade levels. The highest phenol and flavonoid yields per plant were recorded from 30% shade producing high biomass yield, while high phytochemical contents and antioxidant activities were recorded from control plants. The second experiment was conducted to evaluate the effects of different shade levels (0 and 30% shade) and plant density (9, 15 and 25 plants m-2) on shoot-root ratio (SRR) and its relationship with growth, physiology and phytochemical composition. Increasing shade level to 30% significantly affected shoot-root ratio (SRR), total phenolic content (TPC) and total flavonoid content (TFC). Increasing plant density from 9 to 25 plants m-2 resulted in significant decrease in SRR, whereas, TPC and TFC increased. Under stressed conditions in control and high plant density, size of above-ground parts was significantly reduced compared to below-ground parts which resulted in low SRR with high phytochemicals. In the third experiment, the effects of plant density and shade levels were evaluated on growth, physiological attributes, biomass yield and phytochemical contents using split-plot design with four replications. Results showed higher total leaf dry weight (TLDW) and total shoot dry weight (TShDW) from 30% shade with 9 plants m-2 density as reflected in high net photosynthesis rate, total chlorophyll content, leaf area and number of branches. Higher dry weight per square meter, TLDW m-2 and TShDW m-2 were observed from 25 plants m-2 density which were associated with higher leaf area index. High total phenol, total flavonoid and antioxidant activities were also detected due to high C:N ratio and low protein content. The highest yield in phytochemical was recorded from 25 plants m-2 density, implying that this density was the best approach for G. procumbens to balance the trade-off between biomass and quantity of secondary metabolites in achieving high photochemical contents with high biomass yield per unit area. In conclusion, the selection of appropriate light intensity and plant density improves both biomass yield and phytochemical composition of G. procumbens.